2021
DOI: 10.54156/cbe.bej.10.1.247
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Students’ Satisfaction Requirements Using the Kano Model

Abstract: Satisfying students, especially in the service institutions, is a bit complicated due to the diverse and dynamic nature of students when it comes to service provision compared to products. This study thus aimed at stratifying students’ satisfaction requirements at higher learning institutions using the Kano model. Qualitative data were collected from a primary source through interviews and questionnaires. A qualitative approach assisted in collecting forty-six requirements from college students. The Kano model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…These findings align with Mangula's (2013) study that reported that the product quality in TMIs had been meaningly upgraded due to the adoption and being certified by ISO 9001. Quality is a distinctive characteristic or attribute possessed by a product or service (Nzumile and Taifa, 2019, 2021a, 2021b); it thus has to be achieved excellently (Taifa et al. , 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…These findings align with Mangula's (2013) study that reported that the product quality in TMIs had been meaningly upgraded due to the adoption and being certified by ISO 9001. Quality is a distinctive characteristic or attribute possessed by a product or service (Nzumile and Taifa, 2019, 2021a, 2021b); it thus has to be achieved excellently (Taifa et al. , 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Fonte: Kano et al, (1984). Por fim, os atributos reversos são aqueles que trazem insatisfação se presentes no produto ou serviço, sendo recomendado livrar-se deles HSU;HUANG, 2021;QU, 2021;KANO et al 1984;LU et al, 2021;NZUMILE;TAIFA, 2021;TANG;LIN, 2021).…”
Section: Empatiaunclassified
“…Barrios-Ipenza et al studied the health quality of the services in two hospitals in Peru using the Kano model [23]. In another study, the classification of students and their education has been discussed using the Kano model [24]. Furthermore, Chen et al applied the Kano model to the field of education in the COVID-19 pandemic [25].…”
Section: Literature Reviewmentioning
confidence: 99%